Oxidative Stress Research on Huntington's Disease Neurons Using Genetically Encoded Biosensors - Malankhanova, Tuyana; Vasileva, Dayaana; Grigor'eva, Elena; Medvedev, Sergey; Zakian, Suren; Malakhova, Anastasia (KnE Life Sciences, 2022)
Many neurodegenerative diseases, including Huntington’s disease (HD), are associated with oxidative stress in the neurons of the brain. Genetically encoded biosensorsare useful for studying these processesin vitro. Human cell cultures expressing the biosensors can serve as a cell model for developing and testing effective agents that reduce oxidative stress. In this work, transgenes encoding biosensors of glutathione oxidative potential(Grx1-roGFP2) with cytoplasmic and mitochondrial localization were introduced into human induced pluripotent stem cells of a healthy donor and an HD patient using CRISPR/Cas9-mediated genome editing. The cells were subsequently differentiated into medium spiny neurons of the striatum. The expression of the biosensors was detected in the iPSCs, neuronal precursors and mature neurons.The obtained cells could be used to study the redox potential of glutathione in HD neurons and to screen for new drug compounds aimed at reducing oxidative stress. Keywords: genetically encoded biosensors, Huntington’s disease, induced pluripotent stem cells, medium spiny neurons, oxidative stress, glutathione, Grx1-roGFP2